El fundamento de la dimensión exterior del modelo europeo: democracia y derechos humanos - Aldecoa Luzárraga, Francisco (Revista Española de Desarrollo y Cooperación, 2023)
This article presents the importance of democracy and the promotion of human rights in the foreign policy of the European Union, as an external dimension of its particular model.